Long term durability of solid-state supercapacitor based on reduced graphene oxide aerogel and carbon nanotubes composite electrodes. (1st September 2020) - Okhay, Olena; Tkach, Alexander; Staiti, Pietro; Lufrano, Francesco
Abstract: Extensive research efforts are dedicated to the development of high voltage aqueous supercapacitors to solve their low energy density concern. Whilst the operating voltage window is governed by decomposition of water ( i.e. 1.23 V), this can be overcome by levelling potentials of oxygen (OER) and hydrogen (HER) evolution reactions. Here we report the design of a symmetrical supercapacitor (SC) in which the electrodes are fabricated from an ink containing reduced graphene oxide (rGO) aerogel, carbon nanotubes and binder by screen printing method on a conductive carbon cloth. For rGO aerogels, porous graphene oxide is prepared by freeze drying and reduced at 180 °C in vacuum. The solid-state supercapacitor is manufactured with two electrodes and a cation exchange electrolyte membrane and can operate stably at 1.6 V in a neutral environment. The initial supercapacitor power density increases from 61.7 to 602 W kg −1 when the current is raised from 0.1 to 1 A g −1 . During the long-term durability test, the SC energy density decreases from 4.2 to 2.7 Wh kg −1 while the power density reduces from 61.7 to 53.1 W kg −1 . The post-mortem analysis performed by X-ray photoelectron spectroscopy on electrodes demonstrats only small chemical modifications of positive electrode, while negative electrode is insignificantly altered, indicating promising perspectives for the usability of rGO-aerogel-based electrodes in practical supercapacitor applications. The self-discharge of the supercapacitor assessed after 10 000 charge/discharge cycles and 140 h floating at 1.6 V is mainly dependent on the activation contributions, likely due to Faradaic processes, which are more significant than that of diffusional ion species and voltage decay due to ohmic leakage mechanism. The solid-state rGO-based supercapacitor is found to be rather stable even under very stringent durability test, revealing low self-discharge rate that can promote possible commercial applications. Graphical abstract: Image 1 Highlights: Flexible textile electrodes from rGO-aerogels/CNT-composite were developed. High capacitance performance at 1.6 V under very stringent cycling (10 000 cycles). Long-term durability (140 h) and chemical stability under floating conditions and high voltage.